Sustainable Directions in Tourism - Espino-Rodríguez, Tomás (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Within the framework of tourism companies and tourist destinations, the question of sustainability is gaining importance. Tourists are increasingly aware of the importance of sustainability criteria, awarding greater value to sustainable destinations. Sustainability refers to a wide range of aspects related to climate change, the economic organization of tourism, social values or questions, job creation, and the necessary protection of the culture of destinations and the environment. Therefore, there is a need for studies that consider these aspects in order to achieve the sustainable development of tourist destinations. Fundamental to this is discovering to what degree tourism companies and destinations approach these questions in the strategies they use to deal with problems stemming from their attempts to be more sustainable. Conceptual papers and empirical research on the economic, social, cultural, and environmental aspects related to tourism companies and destinations are welcome. Studies that analyze how these questions and the concept of sustainability are included in tourism companies and destinations are necessary in these modern times. This book was established for these reasons, dedicated to examining sustainability in tourism. The papers included in this Special Issue can help us to determine the new directions being addressed in the research on sustainability tourism.